Socioeconomic determinants of oil palm smallholders' awareness towards ganoderma disease - Saras Wathy S Neelamagan (2015)
This research is mainly about the socioeconomic determinants of oil palm smallholders' awareness towards Ganoderma disease. Data was collected from the sampled oil palm smallholders through face to face interview by using structured questionnaire. There were 620 respondents have been interviewed in this study, where 500 smallholders from Sabah and 120 smallholders from Peninsular Malaysia. The data analysis was done by conducting descriptive statistics, reliability test, factor analysis, normality test, Mann Whitney test and Kruskal-Wallis test. The findings of factor analysis show that there were three main factors associated with smallholders' awareness towards Ganoderma disease. The factors are awareness on knowledge of Ganoderma disease and detection methods, awareness on symptoms of Ganoderma disease and control methods and awareness on potential spread of Ganoderma disease. The results of comparison test show that there were significant difference in smallholders' awareness on knowledge of Ganoderma disease and detection methods according to farm location and category of smallholder. The comparison test also show that the oil palm smallholders' awareness on symptoms of Ganoderma disease and control methods were different according to the farm location, category of smallholder, age of respondent, smallholders' main occupation and experience in oil palm. Farm location and experience in oil palm cultivation were also found to be the responsible factors in differentiating the smallholders' awareness on potential spread of Ganoderma disease. The profile on awareness of oil palm smallholders towards Ganoderma disease is very important and useful to the relevant stakeholders and agencies in order to help the smallholders in combating the disease.